Tuber Yield and Physiological Characteristics of Potato Under Irrigation and Fertilizer Application. Issue 11 (17th June 2022) - Bagheri Faradonbeh, Hamid Reza; Bistgani, Zohreh Emami; Barker, Allen V.
ABSTRACT: The effects of water availability in the soil and fertilizer application often strongly affect crop growth. Tuber dry matter yield and physiological characteristics of potato ( Solanum tuberosum L.) were investigated under different irrigation regimes (S1, full irrigation, 100% of water requirement; S2, 75% of water requirement; and S3, 50% of water requirement). Nitrogen treatments were four amounts of urea (N1, providing 100% of N requirement; N2, 66% of N requirement; and N3, 33% of N requirement, and N4, 0 kg N/ha. Drought stress with 50% of the water requirement and limiting nitrogen fertilizer application suppressed the number and weights of tubers per plant. The yield of marketable tubers in S1 and S2 treatments was not significantly different. Treatments N1, N2, and N3 increased the yield of marketable tubers by 37, 33 and 12%, respectively, compared to N4 . Drought stress (S3 ) increased the percentage of dry matter, but nitrogen fertilization did not cause a significant change. Drought stress (S3 ) increased the amount of soluble sugars in tubers and proline in leaves; however, the amounts of soluble sugars and proline were unchanged by increased nitrogen fertilization. Full irrigation and meeting of nitrogen requirements of potatoes led to high chlorophyll concentrations in leaves. Under drought stress (S3 ) and increasing nitrogen, the starch content of tubers was suppressed. The amount of nitrate in the tubers was not affected by irrigation treatments, but was raised by increasing nitrogen fertilization. Irrigation of 75% or more combined with fertilizer application of 66%, was an appropriate treatment for potato production.